2014
DOI: 10.1515/ract-2014-2114
|View full text |Cite
|
Sign up to set email alerts
|

A density functional theory study of the competitive complexation of pyridine against H2O and Cl−− to Cm3+ and Ce4+

Abstract: Density functional theory was used to study the coordination of Cm3+ and Ce4+ with pridine (Py), water (H2O) and chloride anion (Cl−). The competitive coordination of Cl− and Py was investigated to simulate the ligand exchange between Cl− and Py at high concentration of hydrochloric acid (HCl), where Cm3+ and Ce4+ may exist in the form of [CmCl6]3− and [CeCl6]2−, while that of water and Py to simulate the process at low concentration or without the presence of Cl−. The calculations show that Ce4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Evidence of Ce 3+ complexation with anions has been reported for nitrate, , sulfate, , and systems with a high concentration of chloride (14 M), but its structure in MSA has not been studied. The structure of the Ce 4+ complex is unknown in MSA and TFSA, but Ce 4+ is expected to complex with anions in all acids studied here except perchloric acid, where evidence of dimerization has been reported. The structures of Ce 3+ and Ce 4+ are rarely studied in more than one electrolyte per study. Additionally, the methods and conditions at which the cerium ions are studied are varied, which limits the ability to compare structures across acids and extract trends in free energy.…”
Section: Introductionmentioning
confidence: 91%
“…Evidence of Ce 3+ complexation with anions has been reported for nitrate, , sulfate, , and systems with a high concentration of chloride (14 M), but its structure in MSA has not been studied. The structure of the Ce 4+ complex is unknown in MSA and TFSA, but Ce 4+ is expected to complex with anions in all acids studied here except perchloric acid, where evidence of dimerization has been reported. The structures of Ce 3+ and Ce 4+ are rarely studied in more than one electrolyte per study. Additionally, the methods and conditions at which the cerium ions are studied are varied, which limits the ability to compare structures across acids and extract trends in free energy.…”
Section: Introductionmentioning
confidence: 91%
“…We have shown that a structural change in the first coordination shell occurs between the Ce 3+ and Ce 4+ oxidation states, 11 in agreement with the literature showing that Ce 3+ is preferentially coordinated by water in most acids 31 34 and Ce 4+ is complexed by anions in acids. 35 41 The density functional theory (DFT)-calculated energy of this complexation explains the shift in the Ce 3+ /Ce 4+ redox potential with acid. 11 , 23 However, we identified small differences in the extended X-ray absorption fine structure spectroscopy (EXAFS) of Ce 3+ in sulfuric acid compared to other acids, and we were unable to identify the exact structure of Ce 4+ in sulfuric acid through EXAFS, which motivated additional EXAFS studies.…”
Section: Introductionmentioning
confidence: 99%